2023
DOI: 10.4041/kjod22.091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cell viability and antimicrobial effects of orthodontic bands coated with silver or zinc oxide nanoparticles: An in vitro study

Abstract: Objective:We aimed to evaluate the cell viability and antimicrobial effects of orthodontic bands coated with silver or zinc oxide nanoparticles (nano-Ag and nano-ZnO, respectively). Methods: In this experimental study, 30 orthodontic bands were divided into three groups (n = 10 each): control (uncoated band), Ag (silver-coated band), and ZnO (zinc oxide-coated band). The electrostatic spray-assisted vapor deposition method was used to coat orthodontic bands with nano-Ag or nano-ZnO. The biofilm inhibition test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Other components of orthodontic appliances, such as ligature wires, buccal tubes, and orthodontic band strips, have not been discussed in depth. Of course, functional surface coatings for orthodontic bands have recently emerged, such as AgNPs coatings with enhanced antimicrobial properties [ 200 ]. Going forward, each attachment for fixed appliances should be taken into account for future improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Other components of orthodontic appliances, such as ligature wires, buccal tubes, and orthodontic band strips, have not been discussed in depth. Of course, functional surface coatings for orthodontic bands have recently emerged, such as AgNPs coatings with enhanced antimicrobial properties [ 200 ]. Going forward, each attachment for fixed appliances should be taken into account for future improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Palanivel et al [444] also compared the friction forces of SS brackets against uncoated, ZnO-NPs-, or AlO-NPs-coated NiTi archwires, finding that the latter coating type showed an intermediate performance. ZnO-NPs-coated SS bands showed in vitro biocompatibility with HGF cells [364].…”
Section: Metal Oxide-based Nanoparticles Coatingsmentioning
confidence: 95%
“…Similarly, other authors [362] reported a significant decrease in the activity of S. mutans and L. acidophilus after a 24-48 h incubation with Ag-NPs-coated segments of SS orthodontic bands. Ag-NP coatings provide antimicrobial properties to SS brackets [48], bands [363,364] and archwires [365], namely against S. mutans, S. sobrinus, C. albicans, and L. acidophilus [48,364,365]. Coated NiTi archwires induced a more than 90% decrease in the adhesion of S. sanguinis and L. salivaris [366].…”
mentioning
confidence: 99%
“…8,83 The antimicrobial activity of ZnO NPs arises from their ability to induce oxidative stress, disrupt cell membrane integrity, and interfere with cellular functions in microorganisms. 84…”
Section: Antimicrobial Properties Of Zinc Oxide Nanoparticlesmentioning
confidence: 99%